MODEL KEBIJAKAN DAN PELAKSANAAN KEDISIPLINAN SEBAGAI PEMBENTUKAN KARAKTER SISWA DI MTs NEGERI PRAMBANAN KLATEN - Sri Hartini (Universitas Muhammadiyah Ponorogo, 2017)
Model discipline policy imposed to students in MTs Prambanan was state organized in a form of conduct that has been approved and has been socialized to all school stakeholders like teachers, students and caregivers provided scoring offense have been detailing. As for the cause factor student indiscipline, MTs Country Prambanan which were caused by factors largely influenced by family problems in the form of broken family home, family, and educational background are low so that less attention to the issue of education as well as in terms of oversight. Whereas the implementation of the discipline of students in Klaten Prambanan country MTs include: a). Socialization of the code of conduct and rules that apply in the country the effort both Prambanan MTs to all students as well as to the student guided parent; 2.) Provides guidance and counseling to all students; 3). Calling to troubled students; 4). Hold guidance to studentscurative, as well as preventive and corrective manner, identify problems, diagnosis, prognosis, treatment, evaluation, and follow-up. 5.) Development, namely the assessment of current conditions students than ever before; 6) Hold a home visit; 7.) To the Reveral experts. That the number of students of 709 students, there are 20 students in disciplining are removed from the madrasah in the year 2015/2016 this lesson about 2.8% of students who commit offenses are heavy.